ASSESSMENT OF RISK FACTORS FOR THE DEVELOPMENT OF BRONCHOBSTRUCTIVE SYNDROME IN CHILDREN - Umarova Saodat Sulaymonovna; Nabieva Farangiz Sadriddinovna; Niyatkulov Diyorbek G`ayratovich. (Western European Studies, 2024)
Through a retrospective study, we processed 912 medical records of children, aged from 2 months to 5 years, hospitalized in the intensive care unit of pediatrics No. 1 and pediatric intensive care unit of the SFRNCEMP for the period from 2012 to 2015. BOS developed against the background of AOB was diagnosed in 494 (54.2%) children (group 1). In the comparison group, identical in age and gender to the previous one (copy-pair), the diagnosis of OB without symptoms of bronchial obstruction was stated in 418 (45.8%) patients (group 2). In all 494 children, BOS developed against the background of AOB, an acute respiratory disease of the lower respiratory tract.
Keywords: BOS; development of asthma; children